STUDENTS' UNDERSTANDING IMPROVEMENT AND TEAMWORK SKILLS PROFILE AFTER IMPLEMENTATION OF TEAMS-GAMES-TOURNAMENTS (TGT) IN LEARNING FOOD ADDITIVES AND ADDICTIVE SUBSTANCES - Syafiyyah, Fida Zahra (2016)
The aim of this study is to identify students' understanding and teamwork skills in food additives and addictive substances concept after Teams-Games-Tournaments strategy is applied. The method which was used in this research is weak experimental research and one-group pretest-posttest design. The sample used was purposive sampling in an experimental class (n=38 students) with the population of 8th grade students in a Junior High School in Kuningan. Students' understanding was measured using 25 multiple choice questions. Based on Hake's category, the average normalized gain score of pretest-posttest is 0.49 which is categorized as fair. There are only 2 students (5%) of the students who got more than or equal 75 score in pretest, while in posttest, 25 of 38 students (65%) of students pass the minimum standard score. Profile of students' teamwork skill was measured using a teamwork rubric which done through self-assessment and peer assessment and also by observe the student, it is shown that in contribution, problem solving, attitude, focus on task and work with other was good which mean the students have good teamwork skills in their group. The results indicate that Teams-Games-Tournaments can enhance students' understanding and the students have good teamwork skills in food additives and addictive substances concept. Keyword: Teams-Games-Tournaments, students' understanding, teamwork skills, food additives and addictive substances  Tujuan dari penelitian ini adalah untuk mengetahui pemahaman siswa dan kemampuan kerja sama tim dalam konsep zat aditif makanan dan zat adiktif setelah strategi Teams-Games-Tournaments diterapkan. Metode penelitian yang digunakan adalah eksperimen lemah dengan desain one-group pretest-posttest. Sampel penelitian ini adalah satu kelas (n=38) dengan populasi peserta didik kelas 8 di sebuah SMP di Kuningan yang diajukan dengan teknik purposive sampling. Pemahaman siswa diukur menggunakan 25 butir soal pilihan ganda. Berdasarkan kategorisasi Hake, skor gain ternormalisasi yang diperoleh adalah 0.49 yang tergolong dalam kategori sedang. Hanya ada 2 siswa atau 5% yang mendapatkan nilai lebih dari atau sama dengan 75 dalam pretest, sementara dalam posttest 25 dari 38 (65%) siswa lolos KKM. Profil kemampuan kerja sama tim siswa diukur menggunakan rubrik kerja sama tim yang dilakukan dengan cara evaluasi diri sendiri dan penilaian teman sebaya/ peer assessment serta observasi siswa oleh guru, data yang diperoleh menunjukan bahwa dalam hal kontribusi, pemecahan masalah, sikap, fokus pada tugas dan bekerja sama dengan teman satu grup, siswa sudah cukup baik, yang mana berarti siswa memiliki kemampuan nerkeja sama yang baik dalam tim. Hal tersebut menunjukkan bahwa Teams-Games-Tournaments dapat meningkatkan pemahaman siswa dan siswa memiliki kemampuan kerja sama tim yang baik dalam memperlajari dalam konsep zat aditif makanan dan zat adiktif. Kata kunci: Teams-Games-Tournaments, pemahaman siswa, kemampuan kerja sama tim, zat aditif makanan dan zat adiktif